Improvement and utilization of barley straw - Getachew, G.; Tedla, A.; Bediye, S.; Sebsibe, A.; Tsegahun, A.; Berhe, Kahsay (Institute of Agricultural Research, 1996)
Out of 6.5 million tons of crop residues produced each year in Ethiopia, over a million tons of straw comes from barley. There is substantial under utilization of barley straw as animal feed. The major constraints on the use of barley straw as animal feed are low nutrient content, low voluntary intake, poor digestibility, use of straw for other purposes and unavailability of storage facility. The low nutritive value could be upgraded to support increased animal production. There are several factors that affect the quality of barley straw. This paper presents review of previous research work on barley straw quality improvement and utilization in the country.